NIGERIAN CENTRALIZED POLICE STRUCTURE AS AN ANTITHESIS OF COMMUNITY POLICING - Ikedinma, H A (Social Science Research, 2018)
Community policing focuses on crime and social order through the delivery of police services that includes aspects of traditional law enforcement as well as prevention, problem solving, community engagement and partnership. It is a strategy developed to move from what has become “reactive” policing to preventive policing in which the police see themselves, and are perceived by the society as a force at its service not as an agency merely imposing law and order. However, the police structure in Nigeria does not precisely recognize community policing due to centralized nature of its structure. Thus, this article appraises the prevalent nature of centralized police structure in Nigeria to ascertain the effect of centralized structure on the operational needs of community policing in the country. It also examined the dispute over control of the police as well as its possible influence on the insecurity being experienced in Nigeria and; determined the prospects of non-centralized police structure. The objective is to provide information on police reforms centered on community policing that could enhance law and order maintenance as well as crime fighting. The article relied on secondary data and content analysis in analyzing the data. It is underpinned by the principle of subsidiarity.